2020
DOI: 10.1016/j.ccr.2020.213183
|View full text |Cite
|
Sign up to set email alerts
|

Water-oxidizing complex in Photosystem II: Its structure and relation to manganese-oxide based catalysts

Abstract: DOI to the publisher's website.• The final author version and the galley proof are versions of the publication after peer review.• The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 163 publications
(330 reference statements)
0
65
0
Order By: Relevance
“…It was predicted that the chemical diversity and dimensions of the MONs of the Ti-based alloys possess interesting electronic and physical characteristics, which can be modulated for a wide range of purposes [ 71 , 180 ]. From this viewpoint, organized arrays of MONs on Ti–Mn alloy with α + β microstructure can be a prospective material as both TiO2 and Mn2O3 are extensively employed in energy applications [ 181 , 182 ]. In addition to this type of approach, the microstructural properties, mechanical behavior, and biocompatibility of low-cost β-type Ti-(6–18)Mn alloys were examined after the solution treatment, where Ti–9Mn showed the best combination of tensile strength and elongation among the fabricated alloys, and comparable or superior to those of Ti–6Al–4V ELI, for every parameter evaluated.…”
Section: Comparison Between Mono and Mixed Oxide Nanotubesmentioning
confidence: 99%
“…It was predicted that the chemical diversity and dimensions of the MONs of the Ti-based alloys possess interesting electronic and physical characteristics, which can be modulated for a wide range of purposes [ 71 , 180 ]. From this viewpoint, organized arrays of MONs on Ti–Mn alloy with α + β microstructure can be a prospective material as both TiO2 and Mn2O3 are extensively employed in energy applications [ 181 , 182 ]. In addition to this type of approach, the microstructural properties, mechanical behavior, and biocompatibility of low-cost β-type Ti-(6–18)Mn alloys were examined after the solution treatment, where Ti–9Mn showed the best combination of tensile strength and elongation among the fabricated alloys, and comparable or superior to those of Ti–6Al–4V ELI, for every parameter evaluated.…”
Section: Comparison Between Mono and Mixed Oxide Nanotubesmentioning
confidence: 99%
“…In order to elucidate the mechanism of the water-splitting reaction, the structure of PSII has been studied extensively by X-ray diffraction (XRD) with synchrotron radiation (SR) 2 8 and a number of spectroscopic methods including extended X-ray absorption fine structure (EXAFS) and electron paramagnetic resonance measurements 9 . The SR structure of PSII at an atomic resolution revealed that OEC is a Mn 4 CaO 5 cluster organized into a distorted-chair form, in which the cuboidal part is composed of Mn 3 CaO 4 and the outer manganese is attached to the cuboid via two μ-oxo-bridges 6 .…”
Section: Introductionmentioning
confidence: 99%
“… 4 More than 30 different crystalline forms of manganese oxides are found in nature that are spontaneously depleted through water and surface groundwater during the weathering of igneous and metamorphic rocks. 5 These naturally occurring manganese oxides participate in diverse natural chemical reactions and thus determines the arability of soils and sediments, the composition of natural waters, and the potability of both surface and subsurface waters. Complex manganese oxides are very reactive and fine grained materials and govern significant roles that are important to life on Earth, such as transport of minerals, oxygen cycling in the water column, and biomineralization.…”
Section: Introductionmentioning
confidence: 99%